Intervenções psicológicas e comportamentais nos transtornos alimentares caracterizados por compulsão alimentar recorrente associados a sobrepeso ou obesidade - Palavras, Marly Amorim [UNIFESP] (2019)
Background: This thesis is structured in three articles involving the association between Bulimia Nervosa (BN) or Binge Eating Disorder (BED) and overweight/obesity. Current treatments to these clinical conditions usually focus either on improvement of eating disorder symptoms or in weight loss. In this project, we tested a psychological intervention, called HAPIFED, which targets simultaneously binge eating associated to overweight/obesity comparing to the intervention with the best evidence of efficacy, the Cognitive Behavioural Therapy, in its enhanced form (CBT-E). Objectives: Study 1 - presents a systematic review of the literature and meta-analysis evaluating the effects of psychological approaches in the remission or reduction of binge eating and weight loss in obese people with BN or BED. Studies 2 and 3 - describe the protocol of a randomized controlled trial (RCT) which tested the efficacy and safety of HAPIFED compared to CBT-E in reducing symptoms of eating disorders and introducing the healthy management of weight loss in the treatment of obese people with BN or BED. Methods: Study 1 – Articles selected in databases (up to March 2016) consisted of RCTs testing psychological approaches for binge eating remission or reduction and weight loss, in adult population with overweight/obesity and diagnosis of BN or BED. Methodological quality of trials was evaluated and meta-analysis of results of studies comparing CBT with Behaviour Weight Loss Therapy (BWLT) was performed. Studies 2 and 3 - A single blind RCT selected adults of both genders with BN or BED (DSM-5 or ICD-11) and BMI ≥ 27 to < 40 kg/m². Ninety-eight participants were randomized, 50 were included in HAPIFED and 48 in CBT-E. Compared interventions provided 30 group sessions over 6 months. The primary outcome was weight reduction and secondary outcomes included reduction of symptoms of eating disorder. Results: Study 1 - Nineteen articles were included in this review. No study with BN was identified. CBT was the most tested intervention. For binge eating remission, CBT was superior to waiting list, not superior to other interventions and inferior to CBT combined with exercise. For weight loss, CBT was not superior to waiting list or other interventions and was inferior to CBT plus exercise. In meta-analysis comparing CBT with BWLT, CBT promoted greater binge eating frequency reduction at the end of treatment (MD 2.04 95% CI, 0.35 to 3.73; n=4). Meta-analyses performed for binge eating frequency at 12-month follow-up, as well as for weight loss at the end of treatment and 12-month follow-up did not show difference between treatments. Studies 2 and 3 – There was no difference between groups throughout treatment for weight loss (x²(3)=0.19, p=0.979), nor for the secondary outcomes, except for reduction of purging behaviours, favoring HAPIFED (x²(3)=10.35, p=0.016). There was a reduction of eating disorders’ psychopathology in both treatments. Conclusions: Study 1 – Evidence supports better results for CBT with regards to short-term binge eating remission compared to BWLT. Insufficient evidence was found for superiority of BWLT efficacy compared to CBT considering binge eating remission, reduction of binge eating frequency and weight loss in short term. More research is needed to test the efficacy of psychological treatments for BED or BN with co-morbid overweight/obesity, including trials evaluating binge eating remission and weight loss in the long-term. Studies 2 and 3 - HAPIFED was not superior to CBT-E in promoting clinically significant weight loss and was not significantly different in reducing most eating disorder symptoms. No harm was observed with HAPIFED, in that no worsening of eating disorder symptoms was observed.